Studies on very long chain marine n-3 fatty acids in patients with atherosclerotic heart disease with special focus on mechanisms, dosage and formulas of supplementation - Arnesen, H.; Seljeflot, I. (Cellular and Molecular Biology, 2010)
Based on experience from randomised trials with n-3 PUFA we intend to answer some relevant questions in patients with coronary heart disease. In the SHOT study supplementation with 3.4g/day of highly concentrated n-3 PUFA for 1 year significantly reduced the occlusion rate of venous aortocoronary bypass grafts, and this effect correlated significantly to the change in serum levels of n-3 fatty acids. In the CART study 5.1g/day of highly concentrated n-3 PUFA did not reduce the incidence of restenosis after 6 months. If anything, a negative effect was observed. The background for this was probably a prooxidative and proinflammatory mechanism as elucidated in substudies. In the OVITES trial the addition of vitamin E did not counteract the proinflammatory effect of high amounts of n-3 PUFA supplementation as observed in CART, although circulating oxidative substances were unaffected. In the "Fiord-to-table” study replacement of fish oils by vegetable oils in the feed of farmed Atlantic salmon was mirrored in the fatty acid profile of the salmon fillets as well as in that of serum from patients after ingesting about 700g/week for six weeks. A parallel reduction of the proinflammatory profile was observed only in patients who ingested salmon fed on fish oil.